Pembalakan Liar Pemanfataan Hasil Hutan Kayu Oleh CV. Sumber Berkat Makmur pada Hutan Adat Di Desa Sabuai Kota Ambon: Illegal Logging Utilization Of Wood Forest Products By Commanditaire Vennootschap Sumber Berkat Makmur Customary Forests Sabuai Village - Nadya Wardah Mudrikah; Intan Nevia Cahyana (Faculty of Law, Universitas Trisakti, 2025)
The utilization of timber resources in customary forests must have permission if it is to be used for business purposes and must comply with applicable regulations. This is stipulated in Article 50, paragraph (2) of Law No. 41 of 1999 on Forestry. Transporting timber without permission constitutes illegal logging, as regulated in Article 12, letter K of Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction. The issue raised is whether the use of timber in the customary forest area of Sabuai Village by CV. Sumber Berkat Makmur violates the applicable regulations, and whether the judge's considerations in the ruling align with the principles of forest utilization and the impacts of illegal logging. To address this, a normative legal method is used, with secondary data analyzed descriptively and analytically, utilizing qualitative data analysis and deductive reasoning. Based on the result and the conclusion, CV. SBM violated Article 50, paragraph (2) of Law No. 41 of 1999 and Article 12, letter K of Law No. 18 of 2013. Illegal logging occurred outside the permitted area, thus the judge's ruling was appropriate, and sanctions must have a deterrent effect. Illegal logging disrupts environmental sustainability due to forest damage.